The role of media in shaping pro-environmental behaviors: integrating media system dependency theory and norm activation theory - Liao, Chi-Horng (Frontiers in Psychology, 2025)
This study examines how media factors influence pro-environmental behavior (PEB) through an integration of Media System Dependency Theory (MSDT) and Norm Activation Theory (NAT). Using both Fuzzy Decision-Making Trial and Evaluation Laboratory (F-DEMATEL) and Structural Equation Modeling (SEM), it evaluates the effects of media factors on NAT components—awareness of consequences and ascription of responsibility—and their role in activating personal norms that drive PEB. The study also considers the moderating impact of self-efficacy on the link between personal norms and PEB. Findings from F-DEMATEL, based on input from 20 experts, indicate a causal connection between media factors (exposure, attention, dependence, credibility) and NAT variables. SEM analysis from a large sample of 1,594 participants in Taiwan reveals that media factors influence NAT components, with awareness of consequences and ascription of responsibility indirectly affecting PEB via personal norms. However, the direct effects of the ascription of responsibility and personal norms and the awareness of consequences and PEB were not significant, differing from prior research. Additionally, self-efficacy was found to moderate the positive influence of personal norms on PEB. This study contributes theoretical and practical insights, discusses limitations, and offers directions for future research. This research contributes theoretically and practically, highlights limitations, and suggests avenues for future investigation.